(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The centipede cummunities of some apple orchards in Valtellina (northern ltaly, Lombardy, Sondrio) have been studied by means of pitfall traps. Seven species have been collected and some auto- and synecological considerations are given.